Penyertaan kaum wanita dalam keusahawanan luar bandar - Talib, Azlizan; Md. Zan, Zainal; Jusoh, Hamzah; Syed Ibrahim, Sharifah Sofiah 'Atiqah (2013)
Entrepreneurship as catalyst that is believed to be able to change and improve the lives of communities.Thus, the participation of community members in entrepreneurship is deemed necessary and demanded to ensure the effectiveness of the activity, particularly in rural areas. Women participation can help an entrepreneurship grows more rapidly in the direction of generating and improving standard of living of the community. However, the level of women participation in entrepreneurship is still low.Many factors need to be identified in influencing the level of participation of community members in the entrepreneurship.These factors should be examined in depth as they influence the direction of entrepreneurship undertaken.Besides, what other aspects that should be given an attention in generating and encourage women participation in entrepreneurship in rural areas? Through active participation among members of the community, it is hoped that rural entrepreneurship and expansion will continue to move towards another potential source of prosperity and success in rural areas.